The Special Data Dissemination Standard Plus : Guide for Adherents and Users. (Manuals and Guides, 2013)
The International Monetary Fund (IMF) launched the Data Standards Initiatives to enhance member countries' data transparency and to promote their development of sound statistical systems. The need for data standards was highlighted by the financial crises of the mid-1990s, in which information deficiencies were seen to play a role. Under the Data Standards Initiatives, the IMF established the Special Data Dissemination Standard (SDDS) in 1996 to provide guidance to countries that have or seek access to capital markets to disseminate key data so that users in general, and financial market participants in particular, have adequate information to assess the economic situations of individual countries. In 1997, the IMF introduced under the initiatives the General Data Dissemination System (GDDS) to provide a framework for countries that aim to develop their statistical systems, within which they can work toward disseminating comprehensive and reliable data and, eventually, meet SDDS requirements. In February 2012, the IMF Executive Board approved the establishment of the SDDS Plus as a third tier of the Fund's Data Standards Initiatives to address data gaps revealed during the global crisis. The SDDS Plus is open to all SDDS subscribers: those with systemically important financial sectors are encouraged to adhere early to the initiative.